Pengaruh penambahan tepung kunyit dan tepung jahe terhadap performa ayam petelur - Huda, Khoirul; Siswara, Hamzah Nata; Atho’illah, Muhammad Ahsan (Jurnal Sain Peternakan Indonesia, 2023)
This study aims to see the production performance of laying hens fed with turmeric flour and ginger flour. The laying hens used were 80 with Isa Brown strain aged 32 weeks. The maintenance of laying hens in this study was carried out intensively (caged). During the study, chickens were fed twice daily at 08.00 WIB and 15.00 WIB. Feed is given in a measured manner, namely 120 g/head / Day. Drinking water is given in ad libitum measured. The parameters observed in this study are feed intake, hen day production, egg weight and feed conversion ratio. This study used a complete randomized design (CRD) with four treatments and four replications. They were given treatment through feed ration with the following details: P0 (feed), P1 (feed + 0.75% turmeric flour + 0.25% Ginger flour), P2 (feed + 0.25% turmeric flour + 0.75% Ginger flour) and P3 (feed + 0.50% turmeric flour + 0.50% Ginger flour). Giving turmeric flour and ginger flour into the feed had a significant effect on hen day production and egg weight (P<0.05) and no significant effect on feed intake and feed conversion ratio. From the results of this study, it can be concluded that adding turmeric flour and ginger flour can produce hen day production and high egg weight.